Measure, probability, and mathematical finance : a problem-oriented approach - Gan, Guojun, 1979-; Ma, Chaoqun (Professor); Xie, Hong (Financial expert) (Wiley, 2014)
An introduction to the mathematical theory and financial models developed and used on Wall Street Providing both a theoretical and practical approach to the underlying mathematical theory behind financial models, Measure, Probability, and Mathematical Finance: A Problem-Oriented Approach presents important concepts and results in measure theory, probability theory, stochastic processes, and stochastic calculus. Measure theory is indispensable to the rigorous development of probability theory and is also necessary to properly address martingale measures, the change of num.